Analysis of Critical Thinking Ability of High School Students in Sleman Regency on Virus Material - Nurhalis Sidabutar; Ixora Sartika Mercuriani (Jurnal Penelitian Pendidikan IPA, 2024)
The benefits obtained if someone think critically is to make students active and effective in life, they can also develop understanding, evaluate different insights, develop problem solving skills so that later students have the ability to analyze further. The purpose of this analysis is to describe the critical thinking abilities of students in Sleman Regency. This research uses a quantitative descriptive method using an essay with 5 questions referring to indicators of critical thinking. Apart from that, the population in this analysis is all state high schools in Sleman Regency with a purposive random sampling technique of 9 schools, totaling 258 students. The results of the research show that students' critical thinking abilities are in the low category, so it is hoped that innovation will be needed in the form of developing methods, media, strategies and learning models that support students' 21st century abilities, especially in the aspect of critical thinking abilities.